Incidence of a mosaic disease of Sesbania grandiflora caused by a sobemovirus in Andhra Pradesh - and M.V. NAYUDU, S. ERANNA, P.,SREENIVASULU (Indian Phytopathology, 2002)
Sesbania mosaic virus, a member of sobemovirus group, naturally infects Sesbania grandiflora Pers., in Cuddapah district of Andhra Pradesh. Its incidence and spread as studied in Cuddapah district ranged from less than 2.0 to 21.0 per cent in the 6-month old S. grandiflora and in the 12-month old crop, it ranged from 12.0 to 80.0 per cent. The diseased plants were more towards the hedges of the fields with nearby infected old S. grandiflora plants. Mapping diseased plants over 6 months period showed secondary infected plants clustered around primarily infected plants. Sixty other crop and weed plants growing in and around the Sesbania fields were free from the virus. The virus seems to be not seed transmitted.